Rancang Aplikasi Penjualan Online Perlengkapan Anak pada CV. Permata - Sulistiowati, Sulistiowati; Guntoro, Radix Ardi; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV.Permata is a child store with the name of Nikita Baby Shop. CV. Permata located in Gotong Royong street No. 25E, Babat Lamongan. In 2015, sales of CV. Permata instability.CV. Permata must be expanding their sales to get more profit. Based on interviews, CV. Permata do not want to using social media such as facebook and instagram to selling their products. The shortage of facebook and instagram, customers got difficult to booking the products. Of the CV. Permata problem, CV. Permata need online shop application that have add to cart features, product catalogue features, best seller report, most buyer report, product stock report, etc. With this application is expected to provide information data member, best seller report, most buyer report, product stock report with the aim of providing information to help CV.Permata sales.Keywords: Online Shop, Website, Baby Shop